A human beta-actin expression vector system directs high-level accumulation of antisense transcripts. - Gunning, P (1987)
We have constructed a mammalian expression vector consisting of 3 kilobases of the human beta-actin gene 5' flanking sequence plus 5' untranslated region and intervening sequence 1 linked at the 3' splice site to a short DNA polylinker sequence containing unique Sal I, HindIII, and BamHI restriction endonuclease sites followed by a simian virus 40 (SV40) polyadenylylation signal. Two derivatives, containing the selection markers obtained from pSV2gpt or pSV2neo, were also generated. We find that the promoter activity of this vector is a great or greater than that of the SV40 early promoter in a variety of human and rodent cells. The vector was used to generate gamma-actin and beta-tubulin antisense transcripts in human fibroblast cell lines. The antisense transcripts accumulate to levels comparable with that of the highly abundant gamma-actin and beta-tubulin mRNAs.